Implementasi Supervisi Klinis untuk Meningkatkan Profesionalitas Guru - Nelisma, Yuliana; Asmadin, Asmadin; Candra, Indra Abdi; Dasril, Dasril; Jarkasi, Jarkasi (Guidance and Counseling Study Program, Pattimura University, 2022)
The aim of this article is to learn more about how clinical supervision is used to enhance teacher professionalism. Professional teachers are teachers who have the skills to carry out educational and teaching tasks. Thus, the definition of an expert educator is a person who has extraordinary ability and mastery in the field of education so that he can carry out his obligations and abilities as a teacher with maximum abilities. Professional teachers are also educated, trained, and have extensive field experience. This research uses descriptive qualitative research, which is an analysis that uses words or sentences to describe a situation or. The results of research on the use of clinical supervision to improve teacher professionalism at MTsS Hidayatullah, teachers are very flexible, starting from plans that are only communicated to them in regular weekly meetings by the school principal. Only minor problems were encountered, and these problems were not too serious because prospective teachers met the minimum standards when they started at MTsS Hidayatullah. The teacher asks for help to overcome his teaching difficulties, which is why clinical is used here.